NeoFrugivory: A comprehensive database for frugivory interactions and functional traits in the Neotropics - Fuzessy, Lisieux [UNESP] (2025)
Frugivory plays a crucial role in shaping Neotropical ecosystems, influencing plant dispersal, community dynamics, and ecosystem function. Despite its ecological significance, a systematic understanding of frugivore-fruit interactions spanning the entire Neotropical realm has been lacking. Therefore, we compiled the NeoFrugivory database, which addresses this gap by synthesizing data from a wide range of sources, including peer-reviewed literature, field studies, and existing databases. NeoFrugivory represents a comprehensive compilation of 10,175 unique frugivory interactions across the Neotropical region, the most diverse in terms of vertebrate frugivores, and consolidates information from 419 studies spanning from 1967 to 2023. It includes 2375 plant species and 758 terrestrial vertebrate species. In addition to documenting frugivory interactions, NeoFrugivory includes information on functional traits for both plants and vertebrates, such as body mass, diet, fruit morphology, and seed characteristics. The database encompasses diverse terrestrial vertebrate taxa, including species belonging to taxonomic groups such as Primates, Chiroptera, Birds, Artiodactyla/Perissodactyla, Reptilia, Carnivora, Marsupialia, and Rodentia. By providing a centralized repository of frugivory interactions, NeoFrugivory facilitates comprehensive analyses of ecological networks, evolutionary patterns, and ecosystem dynamics across the Neotropics, and NeoFrugivory provides a unique resource for researchers interested in exploring the intricate dynamics of plant–animal frugivory interactions in the Neotropics. This database enables researchers to explore the ecological roles of different frugivore taxa, identify keystone species, assess the resilience of mutualistic networks, and evaluate the impacts of environmental change on fruit-frugivore interactions. Furthermore, NeoFrugivory serves as a valuable resource for conservation practitioners, supporting the design and implementation of targeted conservation strategies aimed at preserving biodiversity and ecosystem function in the Neotropical region. Overall, NeoFrugivory represents a significant advancement in our understanding of frugivory dynamics in the Neotropics and provides a foundation for future research and conservation efforts in this ecologically diverse and critically important region. There are no copyright restrictions on the data; this paper should be cited when data are used in publications.